Tanggung Jawab, Peran, dan Etika Pendidik dalam Perspektif Islam - Muhammedi Muhammedi (Al-Ulum: Jurnal Pendidikan Islam, 2021)
Educators should not cram students' brains with their own ideas or desires. Educators should raise the latent potential contained in students. In the first four years, children subconsciously absorb all ideas and feelings from their social environment. After that, in the next process he began to imitate the attitudes and ideas of the people around him. Here, educators and parents are required to set good examples in their daily behavior and actions, so that they become role models for students in a better direction. An educator should have adequate knowledge about the psychological development of students. This knowledge will really help him to get to know each individual student and make it easier to carry out the teaching and learning process. Educators should have the ability to understand the absorption capacity of students. This ability will be useful for determining educational materials that are in accordance with the abilities of students. If educators impose material beyond the ability of their students, it will cause mental lethargy and even hatred of the science being taught. If this happens, it will hinder the process of achieving educational goals. Therefore, a balance is needed between difficult and easy subject matter in the scope of educational material.